2021
DOI: 10.34172/bi.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Can early treatment of twitcher mice with high dose AAVrh10-GALC eliminate the need for BMT?

Abstract: Introduction: Krabbe disease (KD) is an autosomal recessive disorder caused by mutations in the galactocerebrosidase (GALC) gene resulting in neuro-inflammation and defective myelination in the central and peripheral nervous systems. Most infantile patients present with clinical features before six months of age and die before two years of age. The only treatment available for pre-symptomatic or mildly affected individuals is hematopoietic stem cell transplantation (HSCT). In the animal models, combining bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 54 publications
(53 reference statements)
0
23
0
Order By: Relevance
“…For instance, HSCT has been combined with SRT and/or gene therapy. The combinations consistently yield better outcomes than the matched individual therapies ( 22 , 24 , 25 , 36 ). Other approaches such as ERT, chaperone therapy, and anti-inflammatory therapy also have the potential to contribute as part of combination or standalone therapies.…”
Section: Combination Therapymentioning
confidence: 92%
See 3 more Smart Citations
“…For instance, HSCT has been combined with SRT and/or gene therapy. The combinations consistently yield better outcomes than the matched individual therapies ( 22 , 24 , 25 , 36 ). Other approaches such as ERT, chaperone therapy, and anti-inflammatory therapy also have the potential to contribute as part of combination or standalone therapies.…”
Section: Combination Therapymentioning
confidence: 92%
“…The obstacles include achieving insufficient levels of the corrected enzyme, the blood-brain barrier limiting the delivery of corrected enzyme or viral vector to the CNS, the development of various adverse side effects including some of which are severe, etc. Despite these obstacles, there has been steady progress toward the goal of developing therapies that have increased efficacy, e.g., lengthening of lifespan ( 22 25 ).…”
Section: Experimental Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to greatly extending the lives of treated mice, there was maintenance of body weight and strength, normal myelination in the brain and sciatic nerves, and elimination of the tremor associated with twi mice. More recent studies in twi mice have shown that BMT may not be required if high dose AAVrh10-GALC is given iv early in life [59]. This treatment eliminates some of the side effects of the drugs needed before BMT.…”
Section: Treatment Of the Animal Models Of Krabbe Diseasementioning
confidence: 99%